Effect of surfactant on the size and stability of PLGA nanoparticles encapsulating a protein kinase C inhibitor - Shkodra-Pula, Blerina; Grune, C.; Traege, A.; Vollrath, A.; Schuber, S.; Fischer, D.; Schubert, U. S. (International Journal of Pharmaceutics, 2019)
Nowadays many drugs with improved therapeutic efficacy are discovered but cannot be utilized due to their low solubility and insufficient bioavailability. An example of such a drug molecule is a protein kinase C inhibitor that influences an enzyme which plays an important role in several signal transduction cascades. The aim of this study was to formulate a stable nanoparticle dispersion of the PKC inhibitor encapsulated into PLGA nanoparticles (NPs). Encapsulation of the PKC inhibitor into PLGA NPs of 100–200 nm diameter should provide a targeted delivery to the inflammation sites. The NPs were prepared via nanoprecipitation and different surfactants were investigated: Fully and partially hydrolyzed poly(vinyl alcohol) (PVA, Mowiol X-88 and X-98), poloxamers (Pluronic F68 and F127) and polysorbates (Tween 20 and 80). From all surfactants tested, only NPs prepared with partially hydrolyzed PVA (Mowiol X-88) provided the desired stability throughout the downstream processes. These NPs were subsequently analyzed regarding their particle size, polydispersity, encapsulation efficiency and loading capacity. Dynamic light scattering results revealed that monodisperse NPs of 150–220 nm were formed, a size range that favors targeted delivery. The drug encapsulation efficiency varied from 31 to 75% with a drug loading of 1.3–2%. Moreover, the long-term stability was studied and the residual amount of PVA of the NP solutions was quantified via nuclear magnetic resonance (NMR) measurements. The shell-less hen's egg model was used to test toxic effects (hemorrhage, vascular lysis, thrombosis, hemolysis and lethality) of the NPs in a more complex biological system under dynamic flow conditions.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Encapsulation; Ex ovo hen's egg model; Nanoprecipitation; PLGA nanoparticles; Pluronic; Protein kinase C inhibitor; PVA; Surfactant; Tween